Productive art engagement in a hybrid format: effects on emotions of older adults during COVID-19 pandemic - Magali Payne; Magali Payne; Magali Payne; Kevin Galery; Alexandra Plonka; Alexandra Plonka; Alexandra Plonka; Justine Lemaire; Alexandre Derreumaux; Alexandre Derreumaux; Roxane Fabre; Roxane Fabre; et al. (Frontiers Media S.A., 2024)
IntroductionPrevious studies have shown benefits of productive art-activity on frail older adults' mental and physical health. In this study, we investigated the effects of art-producing activities in a hybrid format (in-person and online) in a context of lockdown compared with previous studies taking place in museums and their effects on wellbeing, quality of life, physical frailty, and apathy in older adults.MethodsWe conducted a randomized unicentric control trial on a sample of 126 seniors older than 65 years (mean age 71.9 ± 2.3, 81% women) living in Nice (France). Participants were randomized in two parallel groups (intervention group with n = 62 vs. control group with n = 64) conducted during pandemic, between March and May 2021. The intervention group involved participatory art-based activities conducted in a hybrid format, either in-person or online, once a week for 2 h over a 12-week period. No specific intervention was proposed to the control group. The main aim was to evaluate how this hybrid format would impact the wellbeing, quality of life, and physical frailty of participants. The secondary aim was to compare our results with the previous studies conducted by Beauchet et al., and the third aim was to evaluate the impact of the intervention on apathy. Validated scales were implemented in RedCap and administered at baseline (M0) and at the end of the third month (M3).ResultsThe intervention group showed significant improvement in their quality of life (p = 0.017) and their level of apathy (p = 0.016) after intervention. Emotional blunting increased significantly in the control group (p = 0.016) while it remained stable in the intervention group. No significant improvement was observed on the frailty, and wellbeing scores remained constant in both groups.ConclusionThis randomized control trial confirmed emotional effects on seniors practicing an art-based activity in a hybrid format during pandemic on a weekly basis for 3 months.Clinical Trial RegistrationClinicalTrials.gov, identifier: NCT04570813.